Oxabicyclic Guest Compounds as sII Promoters: Spectroscopic Investigation and Equilibrium Measurements - Seol, Jiwoong; Shin, Woongchul; Park, Juwoon (Frontiers in Chemistry, 2020)
In this study, we investigate three oxabicyclic compounds, including 3,6-dioxabicyclo[3.1.0]hexane (C4H6O2, ETHF), 7-oxabicyclo[2.2.1]heptane (C6H10O, 14ECH), and 7-oxabicyclo[4.1.0]heptane (C6H10O, 12ECH) as novel promoters for gas hydrates. According to the outcomes of powder X-ray diffraction (PXRD) and synchrotron high-resolution powder diffraction (HRPD), all CH4 hydrates formed with ETHF, 14ECH, and 12ECH were identified to be sII (Fd3-m) hydrates with lattice parameters of 17.195, 17.330, and 17.382 Å, respectively. It was also clearly demonstrated that CH4 molecules are accommodated in the sII-S cages through solid-state 13C NMR and Raman spectra. Consequently, we clearly concluded that the three compounds are large guest molecules (LGMs) that occupy the sII-L cages. Moreover, the thermodynamic stability of each LGM + CH4 (and N2) hydrate system was remarkably improved to compare with that of the simple CH4 (and N2) hydrate. In particular, 14ECH manifested several unique features compared to the other two promoters. First, the 14ECH + CH4 hydrate was not dissociated up to room temperature (298 K), even at a moderate pressure of approximately 60 bar. At a given pressure, 14ECH increased the dissociation temperature of CH4 hydrate by 18 K, indicating that its promotion capability is as strong as that of tetrahydrofuran (THF), currently considered to be the most powerful promoter. Second, more interestingly, it was revealed by further PXRD, NMR, and Raman analyses that 14ECH form a simple sII hydrate in the absence of help gases. In addition to the thermodynamic stability, finally we noted that the 14ECH + CH4 hydrate presented a sufficiently high temperature of formation, requiring little additional cooling. Given these promising features, we expect that the 14ECH hydrate system can be adopted to realize the hydrate based technologies. We also believe that the LGMs introduced here have considerable potentials to serve as alternates to the conventional promoters and that they would be widely utilized in both engineering and scientific research fields.